Anelasticity beneath the Aegean Inferred From Rayleigh Wave Attenuation - Ioannis Kassaras; Filippos Louis; Andreas Magganas; Konstantinos Makropoulos; George Kaviris (Bulletin of the Geological Society of Greece, 2007)
Anelasticity of the Earth crucially affects the propagation of seismic waves especially, in the long period range. However, even though the elastic properties of the Aegean deep lithosphère and upper mantle have been thoroughly investigated, their quantitative anelastic properties that influence the long period wavefield are still largely unknown. This work is towards contributing to the better knowledge of the deep structure of the Aegean by introducing experimental anelastic parameters via the study of long period Rayleigh waves attenuation. For this scope, fundamental mode attenuation coefficients (γ%) have been obtained for different two-station great-circle paths across the Aegean. The data used were provided by a broadband array installed in the area for 6 months in 1997. More than 1100 seismograms were analyzed in the 10-100 s range to obtain 17 sets of path average γR(T) functions. The attenuation coefficients are in the range 2.5*10~3 — 0.15 x 10' km' and correlate sufficiently with both experimental measurements in active tectonic regions elsewhere and synthetics generated with the use of an attenuation reference model inferred from other sources. By applying a stochastic uncoupled causal inversion method an average joint Qß'1 and shear velocity model representative of the under study area was obtained. Furthermore, path average JR(T) functions were combined in a continuous regionalization tomographic scheme to obtain local yR(T) and tomograms were constructed in the range 10-60 s. The most prominent feature in the tomograms is a high attenuation region in the central and north Aegean. This region is located south of the North Anatolian Trough and correlates well with a low shear velocity zone inferred from surface wave phase velocities. Moreover, it is associated with observed intense extensional deformation rates, mantle olivine anisotropy, recent volcanism and high heat flow.